Climate Change and its Impact on Human Health: A Medical Geography Perspective - Wulandari, Agustia Ayu; Pertuak, Anesia Clorita; Rakuasa, Heinrich (PT. Riset Press International, 2023)
This research discusses the impact of climate change on human health using a medical geography approach. Climate change affects health through extreme heatwaves, changing patterns of infectious disease spread and intensification of natural disasters. A medical geography perspective provides insight into how geographical factors such as climate, topography and population distribution affect vulnerability to these impacts. The importance of understanding medical geography in meeting these challenges and the need for global cooperation to address the impacts of climate change on human health are emphasized. The article underscores the need for appropriate mitigation measures to protect future human health in the face of increasingly apparent climate change.